Diseño y aplicación de un manual educativo para el rescate de la identidad cultural que estará dirigido a los maestros de séptimo año de educación básica de escuela “Rafael Moran Malverde” ubicada en el barrio Langaza del cantón Salcedo provincia de Cotopaxi durante el año lectivo 2010/2011 - Guanoluisa Orozco, Carlos Patricio (2015)
This research paper aims to propose a Manual for the rescue of Cultural identity. Given that, the students of the "RAFAEL MORAN VALVERDE" are unaware of the cultural values of their socio-economic environment, critical analytical deductive inductive method was used. To transmit knowledge effectively. We used the interview to the managers, and student survey results which concluded the investigation, obviously is massive ignorance of the students of their own cultural identity. For this reason it is concluded that it is necessary to count with the implementation of a Cultural Identity Manual which provides for raising the self-esteem of their own Cultural identity in children.